Peningkatan proses dan hasil belajar muatan matematika tema 8 subtema 1 melalui model Meaningful Instructional Design (MID) siswa kelas 2 SD Negeri Mangunsari 01 semester II tahun pelajaran 2017/2018 - Marlinda Putri Maharani; Nyoto Harjono; Gamaliel Septian Airlanda (STKIP PGRI Banjarmasin, 2018)
The classroom action research using Kemmis and Taggart model which through 2 cycles, every cycle passing through planning, action-observation, and reflection which aim to see improvement of process and learning outcomes on theme 8 mathematics content using Meaningful Instructional Design (MID). Improved processes are divided into teacher activities and student activities. The subjects of the study were 2nd grade students of SDN Mangunsari 01 with 30 students. The success criteria is ≥75 and 80% of the total studentsare classical, and the learning process is at least good. The research suggerts that: (1) MID learning model can improve the score of learning process. This is seen from the score of teacher activity and student activity cycle I, cycle II. The score of teacher activity in cycle I was 2.94 or 73.5% and 3.68 or 92% in cycle II. While the score of student activity on the first cycle of 2.59 or 64.7% and 3.48 or 87% in cycle II. (2) Improvement of the process impact on improving learning outcomes, seen from the learning completeness in the first cycle of 53.33% or 16 students and cycle II increased to 83% or 25 students. Thus the MID model to improve processes and learning outcomesof mathematics load on 2nd grade students of SDN Mangunsari 01.